Incidence of obesity in female patients with fecal incontinence - Bussen, Dieter G.; Herold, Alexander; Bussen, Stefanie (Visceral medicine, 2012)
Background: The aim of this study was to evaluate the correlation between body mass index (BMI) and the incidence of fecal incontinence in female patients. Patients and Method: In this study, data of 98 female patients presenting with fecal incontinence and of 98 healthy control subjects were retrospectively analyzed. Results: In 34% of the study patients and 50% of the controls, body mass indices were within the normal range (BMI 18.5-24.9 kg/m2) (Mann-Whitney U test: p > 0.05). 29% of the study patients and 32% of the control group were overweight (BMI 25.0-29.9 kg/m2) (U test: p > 0.05). 26% of the study group and 9% of the control collective were identified as obese according to the WHO classification I (U test: p = 0.033). 5% of the patients and 6% of the controls were diagnosed as obese according to the WHO classification II (U test: p > 0.05), and 2% of the patients and 1% of the controls fulfilled the definition for obesity based on the WHO classification III (U test: p > 0.05). Conclusion: Since the percentage of females suffering from obesity is significantly higher in patients presenting with fecal incontinence when compared to healthy controls, weight loss should be pointed out strongly in a conservative treatment of fecal incontinence.
Online publiziert: 16. August 2012
Gesehen am 15.06.2018